Bacterial and Fungal Proteolytic Enzymes: Production, Catalysis and Potential Applications - Silva, Ronivaldo Rodrigues da [UNESP] (Humana Press Inc, 2017)
Submerged and solid-state bioprocesses have been extensively explored worldwide and employed in a number of important studies dealing with microbial cultivation for the production of enzymes. The development of these production technologies has facilitated the generation of new enzyme-based products with applications in pharmaceuticals, food, bioactive peptides, and basic research studies, among others. The applicability of microorganisms in biotechnology is potentiated because of their various advantages, including large-scale production, short time of cultivation, and ease of handling. Currently, several studies are being conducted to search for new microbial peptidases with peculiar biochemical properties for industrial applications. Bioprospecting, being an important prerequisite for research and biotechnological development, is based on exploring the microbial diversity for enzyme production. Limited information is available on the production of specific proteolytic enzymes from bacterial and fungal species, especially on the subgroups threonine and glutamic peptidases, and the seventh catalytic type, nonhydrolytic asparagine peptide lyase. This gap in information motivated the present study about these unique biocatalysts. In this study, the biochemical and biotechnological aspects of the seven catalytic types of proteolytic enzymes, namely aspartyl, cysteine, serine, metallo, glutamic, and threonine peptidase, and asparagine peptide lyase, are summarized, with an emphasis on new studies, production, catalysis, and application of these enzymes.
Keywords: Bacteria; Bioprocess; Biotechnology; Fungi; Lyases; Proteolytic enzymes